Insanity and crime - Molony, Thomas F., Sir (Statistical and Social Inquiry Society of Ireland, 1925)
In July, 1922 Lord Birkenhead, the then Lord Chancellor of Great Britain, appointed a committee of distinguished jurists "To consider and report what changes, if any, are desirable in the existing law, practice and procedure relating to criminal trials in which the plea of insanity as a defence is raised, and whether any and, if so, what changes should be made in the existing law and practice in respect of cases falling within the provisions of Section 2 (4) of the Criminal Lunatics Act, 1884."
Read Friday, February 15th, 1924.]
Keywords: Insanity plea; Penal system; 314.15